Redwood summer - Rickey, Stuart; Rickey, Stuart; Redwood Summer Partners (Oley, PA : Bullfrog Films, 1993)
Presents a season of public demonstrations and civil disobedience actions against Northern California timber corporations by the environmental action group Earth First
Title from title screen
Copy in DVD Format
Editors, Sandra Adair, Mark Baldwin, Meri Weingarten
Narrator: Blair Bess
VHS Format
Keywords: Environmentalism -- Northern California; Forest conservation -- Northern California; Anti-environmentalism -- Northern California